NEXUS Gains Talk 16: Water is life, water is food: A nexus approach to water productivity that leaves no one behind - Lankford, B.A.; Koirala, Sanju; Amarasinghe, Upali A.; Mabhaudhi, Tafadzwanashe (CGIAR System Organization, 2023)
Food and nutrition security can only be achieved with sufficient water of adequate quality, quantity, and reliability. Lack of adequate water affects not only food production, but all components of food systems. Moreover, uncoordinated food and water security strategies limit progress on SDG2 on zero hunger and SDG6 on water and sanitation. Identifying and assessing solutions that jointly support water and food security, and monitoring progress on water–food systems linkages are critical as climate extremes and other stressors increasingly threaten access to water for all. This NEXUS Gains Talk discusses the role of water productivity in ensuring that water is used in ways that supports food security and nutrition and leaves no one behind.